The Utilization of Digital Media in Marketing Ecotourism Packages in Sekotong, Lombok Barat Regency, NTB Province, Indonesia - Isna Haerunnisa; Rumba Rumba; Endang Sri Wahyuni; Achlan Fahlevi Royanow (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Digital marketing as a business trend in branding is a crucial component in marketing products, services, or brands using various digital platforms to expand the market share globally. In the tourism industry, every tourism product must effectively utilize digital media. Sekotong, as a destination known for its ecotourism, needs to leverage digital media optimally to market its ecotourism packages. However, the reality is that the available potential has not been packaged into a single ecotourism package, and its digital promotion for marketing is still not optimal due to the community's lack of understanding on how to manage digital marketing platforms. To comprehend the phenomenon under examination, this study employs a qualitative technique with a case study strategy, while the time horizon is covered by a cross-sectional approach. Data were collected through 3 methods such as: observation, interviews, and documentation. The collected data were reduced and analyzed using content analysis, data validity ensured through those methods and sources triangulation. The results of this study is indicate the utilization of digital media concerning time, cost, and accessibility in marketing ecotourism packages in Sekotong is not optimum implemented, even it has 3 Mangroves forest as its attraction. These are obstacle factors such as limitation of budget, lack of knowledge related digital platform navigation for marketing, and the most importance is stakeholder or tourism Penta-helix coordination and collaboration to develop digital marketing training and sustainable marketing program. The data from this study provide important contributions to tourism practitioners and researchers in developing more effective marketing strategies to promote local ecotourism destinations